Teaching and Learning about Food Hygiene in Primary Education: a Systematic Review - Castellar Cárdenas, Marta; Romero López, María del Carmen; Jiménez Tejada, María del Pilar (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
A systematic review has been carried out following the PRISMA protocol to characterize the scientific production of food hygiene teaching in Primary Education. Bibliometric indicators and research methodologies used are analyzed. The search was carried out in the Web of Science database. Only 12 articles met all the inclusion criteria. There are few publications on food hygiene at this stage, being qualitative studies, co-authored and mostly belonging to the health sector. There is a need to increase research especially in the educational field and to introduce food hygiene in teacher training.